2020
DOI: 10.1177/0269215520911420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a staff behaviour change intervention to increase the use of ward-based practice books and active practice during inpatient stroke rehabilitation: a phase-1 pre–post observational study

Abstract: Objective: The aim of this study was to evaluate a staff behaviour change intervention to increase the use of ward-based practice books and active practice by stroke inpatients. Design: This is a pre–post observational study. Setting: This study was conducted in a inpatient rehabilitation unit in Australia. Subjects: Stroke inpatients participated in the study. Intervention: A staff behaviour change intervention was designed to support staff to implement practice books. The intervention included staff training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This study has attempted to design a novel co-creation method through the integration of a co-production design framework with the BCW steps to co-create digital stories and apply it to identify core collective lessons through the synthesis of individual stroke survivors' experiences of interacting with healthcare professionals. Studies have shown the benefits of including stroke survivors and caregivers within the design process in order to develop more relevant and effective outcomes that emanate directly from the experiences of those who the intervention concerns most (65)(66)(67)(68). The design of this study has placed the input of stroke survivors at the center of the co-creation method, which has subsequently resulted in the synthesis of six important collective lessons that help to detail the presence of preconceptions and attitudes embedded within healthcare that may be negatively impacting survivors' healthcare experiences, and the need for survivors' individual lived experiences to be acknowledged to achieve a truly person-centered approach throughout the stroke pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This study has attempted to design a novel co-creation method through the integration of a co-production design framework with the BCW steps to co-create digital stories and apply it to identify core collective lessons through the synthesis of individual stroke survivors' experiences of interacting with healthcare professionals. Studies have shown the benefits of including stroke survivors and caregivers within the design process in order to develop more relevant and effective outcomes that emanate directly from the experiences of those who the intervention concerns most (65)(66)(67)(68). The design of this study has placed the input of stroke survivors at the center of the co-creation method, which has subsequently resulted in the synthesis of six important collective lessons that help to detail the presence of preconceptions and attitudes embedded within healthcare that may be negatively impacting survivors' healthcare experiences, and the need for survivors' individual lived experiences to be acknowledged to achieve a truly person-centered approach throughout the stroke pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The studies also frequently utilized discrete implementation strategies from the following two clusters: use evaluative and iterative strategies and develop stakeholder interrelationships. Seventeen studies implemented strategies in the evaluative and interactive strategies cluster (40,42,(44)(45)(46)(47)(48)(49)(51)(52)(53)(54)(55)(56)(57)(58)(59), with [4] Assess for readiness & identify barriers & facilitators being implemented the most within this cluster. Discrete strategies from the develop stakeholder relationships cluster were used in 12 studies (37,39,40,43,44,46,49,50,52,56,60,61), with [35] Identify & prepare champions being implemented the most with 7 studies (39,43,44,46,49,56,61).…”
Section: Synthesis Summarymentioning
confidence: 99%
“…Among the eight studies that implemented discrete strategies categorized in the support clinicians cluster, only two different discrete strategies were used. The strategy, [58] Remind clinicians, was almost exclusively used, with seven out of eight studies only implementing this strategy. The one remaining study utilized the discrete strategy [30] Develop resource sharing agreements.…”
Section: Synthesis Summarymentioning
confidence: 99%
See 2 more Smart Citations